Kepemimpinan Kepala Desa Perempuan Di Desa Sungai Dua Indah Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Gayos Alfajri; Afrizal Afrizal; Doni Syahputra; Musthofa Habli (Penerbit Jurnal Indonesia, 2026)
Abstract: This study aims to determine the commitment, complexity, and credibility of the leadership of female village heads in Sungai Dua Indah Village, Rambah Hilir District, Rokan Hulu Regency. The research approach combines qualitative and quantitative methods with descriptive design. The sample consisted of 12 informants selected by census, including village heads, village officials, and community leaders. Data collection techniques include questionnaires, observations, interviews, and documentation, while data validation is carried out through member checks. Data analysis is directed at reduction, presentation, and drawing conclusions. The results show that: (1) The commitment of female village heads is reflected in policy consistency, improvement of services and development, and generosity; (2) Complexity is influenced by socio-cultural and family aspects; (3) Credibility is built through transparency, accountability, and public trust. These findings contribute to government science, particularly in strengthening women's leadership at the village level. Keywords: leadership, village head, women